Time Pattern Locking Scheme for Secure Multimedia Contents in Human-Centric Device - Hyun-Woo Kim; Jun-Ho Kim; Jong Hyuk Park; Young-Sik Jeong (The Scientific World Journal)
Among the various smart multimedia devices, multimedia smartphones have become the most widespread due to their convenient portability and real-time information sharing, as well as various other built-in features. Accordingly, since personal and business activities can be carried out using multimedia smartphones without restrictions based on time and location, people have more leisure time and convenience than ever. However, problems such as loss, theft, and information leakage because of convenient portability have also increased proportionally. As a result, most multimedia smartphones are equipped with various built-in locking features. Pattern lock, personal identification numbers, and passwords are the most used locking features on current smartphones, but these are vulnerable to shoulder surfing and smudge attacks, allowing malicious users to bypass the security feature easily. In particular, the smudge attack technique is a convenient way to unlock multimedia smartphones after they have been stolen. In this paper, we propose the secure locking screen using time pattern (SLSTP) focusing on improved security and convenience for users to support human-centric multimedia device completely. The SLSTP can provide a simple interface to users and reduce the risk factors pertaining to security leakage to malicious third parties.